Joseph Conrad’s ‘Youth’: A Melting Pot for the Old and New - Samir Elbarbary (Cahiers Victoriens et Edouardiens)
Conrad’s short story ‘Youth’ is interestingly complex in its weaving together of disparate fictional elements old and new. The old is prominent in the manipulation of narrative framing in multi-layered narratives intertwined with the intimate act of telling and listening to oral stories. Besides, Conrad evokes the standard seafaring story of far-away lands, adapting and yet simultaneously destabilizing it. The modern/postmodern is at work in a dialogic disposition (in the Bakhtinian sense) along with the shifting discourse that characterizes Conrad’s oeuvre, a metafictional quality, intertextual space, and there is the sense of loss and pointlessness of striving that is fairly common in such writing. Further, the text anticipates the general orientation of postmodernism in conflating heterogeneous discourses. This, in effect, grants depth to the narrative, and opens it up to a new understanding.